Our world : a collection of beautiful photos from around the world - Jeevatharshan, Arulanantham; Karimshah, Atiya; Prashanth, Donbosco; Bueno, Johana; Nguyẽ̂n, Johnny; Thanabalasingam, Krushanth; Quimbaya, Mayra Alejandra Abadia; Dũng, Nguyẽ̂n Ngọc; Ahmed, Shabnaaz Sheik; Vik, Trine; Krushanth, Ameera ([Crestmead, Queensland] : 1000 Tales Co-op Ltd., 2017)
Our World is a collection of beautiful photos from around the world. The photographers were asked to submit photos that reflect their lived experience. The accompanying stories give a small insight into what life is like behind the lens. From the natural to the social and political, this book represents a small part of the enormously diverse world that we live in.
Keywords: Photobooks; Photographers